Achieving Ultra‐Stable All‐Solid‐State Sodium Metal Batteries with Anion‐Trapping 3D Fiber Network Enhanced Polymer Electrolyte. Issue 16 (20th January 2023) - Guo, Junhong; Feng, Fan; Zhao, Shiqiang; Wang, Rui; Yang, Meng; Shi, Zhenhai; Ren, Yufeng; Ma, Zifeng; Chen, Suli; Liu, Tianxi
Abstract: All‐solid‐state sodium metal batteries paired with solid polymer electrolytes (SPEs) are considered a promising candidate for high energy‐density, low‐cost, and high‐safety energy storage systems. However, the low ionic conductivity and inferior interfacial stability with Na metal anode of SPEs severely hinder their practical applications. Herein, an anion‐trapping 3D fiber network enhanced polymer electrolyte (ATFPE) is developed by infusing poly(ethylene oxide) matrix into an electrostatic spun fiber framework loading with an orderly arranged metal‐organic framework (MOF). The 3D continuous channel provides a fast Na + transport path leading to high ionic conductivity, and simultaneously the rich coordinated unsaturated cation sites exposed on MOF can effectively trap anions, thus regulating Na + concentration distribution for constructing stable electrolyte/Na anode interface. Based on such advantages, the ATFPE exhibits high ionic conductivity and considerable Na + transference number, as well as enhanced interfacial stability. Consequently, Na/Na symmetric cells using this ATFPE possess cyclability over 600 h at 0.1 mA cm −2 without discernable Na dendrites. Cooperated with Na3 V2 (PO4 )3 cathode, the all‐solid‐state sodium metal batteries (ASSMBs) demonstrate significantly improved rate and cycle performances, delivering a high discharge capacity of 117.5 mAh g −1 under 0.1 C and rendering high capacity retention of 78.2% after 1000 cycles even at 1 C. Abstract : The anion‐trapping 3D fiber network enhanced polymer electrolyte (ATFPE) is designed to achieve ultra‐stable ASSMB, which can not only successfully construct continuous and fast Na + transport channel, but also effectively regulate uniform Na + concentration distribution for constructing stable anode interface. Consequently, all‐solid‐state Na metal batteries using the ATFPE show significantly boosted cycling performance and rate capability.